Pengaruh Motivasi, Kompensasi Dan Lingkungan Kerja Terhadap Produktivitas Karyawan Bagian Produksi Pada PT. XYZ - Zarkasi, Muhammad Rifqi; Baskoro, Heru; Saefuloh, Asep (Jurnal Mahasiswa Manajemen, 2024)
Background - Companies want to succeed in their business. Companies must be able to develop their human resources in order to drive progress for the company. Productivity is a very old concept, but it is still relevant today. The renewed interest in productivity reflects public awareness of the impact of productivity on economic growth, living standards, and competitiveness. PT XYZ has not achieved its production target for the past three years, indicating compromised productivity. Objectives - This study aims to look at employee productivity at PT XYZ by looking at motivation, compensation, and work environment as variables that support or weaken productivity. Design / Methodology / Approach - In this study, the approach used is a quantitative approach. Data collection in the form of a questionnaire was used to obtain data. Multiple linear regression was used to test the truth of the hypothesis proposed in the study. Findings - Motivation has been shown to have an effect on productivity. Compensation has been shown to have no effect on productivity. The work environment has been shown to have no effect on productivity. Research Implications - This study provides an overview of productivity in companies that can be supported by employee motivation, but not by compensation and work environment. PT XYZ has homework to restore the rhythm of its employees' work productivity by stabilizing the work environment and providing compensation.